A Cys2His2 Zinc Finger Transcription Factor BpSZA1 Positively Modulates Salt Stress in Betula platyphylla - Zhang, Xi; Guo, Qing; Qin, Linlin; Li, Li (Frontiers in Plant Science, 2022)
Zinc finger proteins (ZFPs) are widely involved in plant growth and abiotic stress response, but have not been explored in woody plants. In this study, a gene encoding a C2H2-type ZFP from B. platyphylla (gene BpSZA1) was cloned and characterized. BpSZA1 is a transcription factor that localized in the nucleus, and the transcription activation domain was located at the N-terminus. BpSZA1 was predominantly expressed in stems and was induced by salt. We generated overexpression (OE) and RNAi slicing (Ri) transgenic birch plants and OE lines, Ri lines, and wild type (WT) birch seedlings were exposed to salinity. The phenotypic and physiological parameters such as superoxide dismutase (SOD), peroxisome (POD), H2O2 content, proline content, and malondialdehyde (MDA) content were examined. Overexpression of BpSZA1 in birch conferred increased salt tolerance. Chromatin immunoprecipitation-qPCR and RNA-seq showed that BpSZA1 could bind to the GAGA-motif in the promoter of downstream target genes including APX1, APX2, CAT1 and 6PGDH to active their transcription. And BpSZA1 can also participate in ABA synthesis, proline synthesis, ABA/jasmonic acid (JA) pathway to enhance the salt stress of B. platyphylla.